Application of Artificial Intelligence in FinTech: The Decision of Youth Investors to use Robo-Advisor Platform as Micro-investing Alternative - Ruslan, Rafiatul Adlin Hj Mohd; Ibrahim, Muhammad Azman; Abd Hamid, Nor Harlina (Journal of Entrepreneurship, Business and Economics, 2022)
In light of the emergence of artificial intelligence in financial technology and the fourth industrial revolution, this study aims to propose a research framework on the decision of youth investors in Malaysia to use robo-advisors. This study will examine the youth investor characteristics and robo-advisor characteristics that may influence youth investors' usage of robo-advisor platforms. Technological advances and knowledge-intensive activities increasingly drive economic growth; therefore, research on factors affecting the use of robo advisors should be performed to understand why more young people are investing in digital platforms. This objective will be answered using logistic regression throughout the study. Research paper Keywords: Artificial Intelligence, Financial Technology, Logistic regression, Micro-investing, Robo-advisor Reference to this paper should be made as follows: Ruslan, R. A. H. M., Ibrahim, M. A., Abd Hamid, N. H. (2022). Application of Artificial Intelligence in FinTech: The Decision of Youth Investors to use Robo-Advisor Platform as Micro-investing Alternative. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 38–54.